Characteristics of lowland grasslands used in transhumant sheep systems of Marche region (Central Italy) - Budimir K.; Trombetta M.F.; Avanzolini P.; Iezzi G.; Francioni M.; Toderi M.; Sedic E.; Trozzo L.; Santilocchi R.; D'Ottavio P. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
The paper aims to analyse botanical composition, DM (dry matter) yield and chemical composition of lowland grasslands to evaluate their effect on growth performances of lambs of three breeds (Bergamasca, Sopravissana and Merinizzata) in Marche region. An experimental flock (lambs and ewes of all monitored breeds) grazed four plots differing in site conditions, management and forage characteristics. In each plot, the following grassland characteristics were assessed: botanical composition (at the beginning of grazing), forage DM yield and chemical composition (at the beginning and at the end). To calculate average daily gain (ADG), lambs of each breed were weighed at birth and every 20 days until the slaughter, performed at 60 days of age. Plot 1 was dominated by grasses (mainly, Lolium multiflorum), plots 2 and 3 by legumes (mainly, Medicago sativa), while plot 4 was mainly dominated by forbs (among all, Veronica hederifolia). The comparison of DM yield and chemical composition at the beginning and at the end of the grazing period within each plot revealed significant differences regarding some of the parameters. No statistical differences in live weight and ADG were observed among breeds. ADG during the whole period amounted to 323, 324 and 234 g d-1 for Bergamasca, Sopravissana and Merinizzata, respectively
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)